Implementasi Kebijakan Pengungkapan Sukarela Di KPP Pratama Depok Cimanggis Tahun 2022 Dalam Rangka Meningkatkan Penerimaan Pajak - Firda Oktafiyani; Selvi Selvi (Jurnal Ilmu Administrasi Publik, 2022)
The purpose of this study is to analyze how the implementation of the voluntary disclosure policy at Depok Cimanggis Small Taxpayers Office, to identify implementation challenges, and to learn about initiatives taken by the organisation to address these challenges in order to raise tax revenue. This study employs a descriptive qualitative methodology through documentation and interviews with extension staff at KPP Pratama Depok Cimanggis, tax consultants, academics and taxpayers. The findings of this study showed that Depok Cimanggis Small Taxpayers Office implemented its voluntary disclosure policy correctly and consistently supervising the program's completion by incorporating all workers in its socialisation from January to June 2022. It is important to explain to taxpayers how the Voluntary Disclosure Program's rates compare to those of normal rates in order to pique their interest in taking part in the program. Government supervision over taxpayers who violate the tax code must be strong in order to improve compliance. Along with including stakeholders and the outside environment in policy socialization activities that can help voluntary disclosure policies be implemented.